Verb and object order in the history of English a language-internal account - De Bastiani, Chiara (CAMBRIDGE SCHOLARS PUBLIS, 2020)
This study takes up the challenge posed by the reanalysis of Verb-Object order as the basic one in the history of English; the question, which has been debated for over thirty years, is tackled here by combining a qualitative and quantitative investigation with current linguistic theories, shedding new light on the phenomenon. It introduces new evidence in favour of a universal base order, by exploring the syntax of both Old English and Early Middle English and the information structural and prosodic properties of objects. It also considers the philological history of the texts examined, highl.